Inventing the Past, Creating the Nation: The Contribution of Diosdado Caballero - Nuria SORIANO MUÑOZ (Cuadernos Dieciochistas)
The Majorcan Jesuit, Ramón Diosdado Caballero (1740-1829), became one of the most passionate defenders of Spain, of its historical past, and in particular, of the Spanish colonial regime. A large part of his written work focused on the development of an ideological discourse, strongly characterized by a constant desire for glorification and a fervent Catholicism. At the same time it was accompanied by a marked conservatism that had Bartolome de Las Casas as its main enemy. The case of Diosdado Caballero, comparable to some of his fellow Ignatians, helps us to approach the complex process of key national memory and identity construction that took place in the second half of the eighteenth and early nineteenth centuries, in which Las Casas played a fundamental role.